2010
DOI: 10.2196/jmir.1281
|View full text |Cite
|
Sign up to set email alerts
|

Online Communication Between Doctors and Patients in Europe: Status and Perspectives

Abstract: BackgroundUse of the Internet for health purposes is steadily increasing in Europe, while the eHealth market is still a niche. Online communication between doctor and patient is one aspect of eHealth with potentially great impact on the use of health systems, patient-doctor roles and relations and individuals’ health. Monitoring and understanding practices, trends, and expectations in this area is important, as it may bring invaluable knowledge to all stakeholders, in the Health 2.0 era.ObjectiveOur two main g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 35 publications
6
87
0
2
Order By: Relevance
“…The context can be viewed from different perspectives, including culture, leadership and evaluation, all of which must be taken into consideration before implementation (Rycroft-Malone, 2004;Cummings et al, 2007;2010;Carlfjord et al, 2010). To achieve more efficient implementation, the context must be prepared in advance.…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…The context can be viewed from different perspectives, including culture, leadership and evaluation, all of which must be taken into consideration before implementation (Rycroft-Malone, 2004;Cummings et al, 2007;2010;Carlfjord et al, 2010). To achieve more efficient implementation, the context must be prepared in advance.…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…Among those using the Internet for health-related purposes, more than 40% considered the provision of these electronic health services to be important when choosing a new doctor. 17 In a further study, a group of adolescents uploaded the data from their insulin pumps to their clinic from home and were then provided with interventions by their healthcare team via Skype and Facebook, whereas another group downloaded the data from their pump at regular clinic visits, during which interventions were given in person by their healthcare team. The researchers concluded that where new technologies can examine diabetes management similar to regular clinic visits, adolescents reported preferring to communicate with their healthcare providers using SNS.…”
Section: Sns and Adolescent Diabetes Carementioning
confidence: 99%
“…Internet peut aussi être mobilisé comme support à la communication entre les soignants et les patients (Bjoernes et al, 2012), mais cette pratique est là aussi très peu développée d'une part, parce que les soignants doivent apprendre à engager une discussion sur Internet avec leur patient, et d'autre part, parce que les ordres professionnels sont encore réticents à cautionner ces modes d'interaction, surtout s'ils mobilisent les médias sociaux (Devi, 2011 ;Méadel et Akrich, 2010 ;Oudhoorn, 2008). Des enquêtes internationales soulignent pourtant qu'il s'agit d'une demande d'une part importante de la population dans plusieurs pays (Santana et al, 2010 ;McDaid et Park, 2010). Les usagers apprécieraient, entre autres, pouvoir prendre rendez-vous en ligne, communiquer avec leurs soignants entre deux rendez-vous pour poursuivre la prise en charge initiée lors de consultations en face à face et recevoir les résultats de leurs tests par courriel.…”
Section: Gestion Du «Patient Informé» Et Intégration D'internet Dans unclassified